(untitled) (CONTINUIDAD Y DISCONTINUIDAD EN EL ESPACIO IBEROAMERICANO, 2026)
In 1933, in Argentina, Federico García Lorca presented “Theory and Play of the Duende.” In this lecture, the writer analyzes three figures of poetic inspiration: the “angel,” the “muse,” and the “duende.” Although he comments on all of them, he focuses on the latter due to its influence on Andalusian culture and its inherent tension and incomprehensibility within philosophical analysis.Likewise, García Lorca points out that the duende implies the proximity of death. Based on this link, the poet indicates that one of the countries sharing this preoccupation with death is Mexico. In this sense, the text infers a poetic conception that also impacts a communicative system and, therefore, correlates with the foundations of a social system that transcends the Spanish context.Under this framework, this paper aims to demonstrate the effects of a model of aesthetic inspiration (the “duende”) on the development of political thought. To this end, García Lorca's text will be reviewed alongside related philological analyses. Additionally, Derrida's texts, Specters of Marx and “Che cos’è la poesia,” will be used to discuss the association of the “duende” with the Derridean specter. Finally, pieces by Jaime Sabines and Xavier Villaurrutia will be examined to compare the contemporary Mexican imagery and context.The first part analyzes Lorca's conception of the duende. The second section discusses the political aspects and their relationship with the Derridean ghost. The third section addresses the association of this construct with Mexican poetry and imagery. Finally, the paper concludes with the configuration of a politics of the duende that pertains to the Hispanic order.